Numerical Simulation Of Nitrous Oxide And Carbon Monoxide Abatement In The Catalytic Converter Of A Compressed Natural Gas Engine - Cheong, Yoon Kwan (2008)

(untitled)
Air pollution in Malaysia is mainly caused by emission from motor vehicles according to the Department of Environment (DOE). The Malaysia Government through DOE has been regulating vehicles emissions with more stringent regulations on nitrogen oxides and carbon monoxide emissions gazetted since 1996. Catalytic converters are one of the effective devices to reduce air pollution by motor vehicles by transforming nitrogen oxides and carbon monoxide in the exhaust to relatively harmless nitrogen and carbon dioxide respectively. A catalytic converter is easy to fit into any exhaust system, not bulky and does not require much maintenance. However, due to the presence of precious group metals such as platinum, rhodium and palladium as catalysts, the cost of the catalytic converter is relatively high. Furthermore, the catalysts’ activation and deactivation levels is highly dependent on temperature, hence the design of catalytic converter in the vehicle exhaust system is not easy. The objective of this study is to carry out simulation via CFD code FLUENT 6.0, on catalytic converter design and efficiency in a cold start natural gas engine for nitrogen monoxide and carbon monoxide emission control. CFD code FLUENT 6.0 was used for prediction of catalytic converter light-off temperature and efficiency. Cold start and light-off temperatures are the acceptable worst scenario for compressed natural gas (CNG) engine pollutants abatement in order to achieve low emission vehicle. The simulation result was then verified via experimental data published in the literature. Another CFD modelling module was conducted to predict the exhaust gas temperature at 10cm, 30cm, 50cm, 80cm and 110cm from the engine outlet to determine the best position of catalytic converter in the exhaust system. A third CFD modelling module was done to simulate the surface reactions on a single channel of a catalytic converter. This is the contribution to the knowledge in the pollutants abatement in catalytic converter. The simulation result was then verified via experimental data published in the literature. The simulation of catalytic converter light-off temperature for NO and CO were proved to be satisfactory when compared to presented experimental result. Simulated NO conversion efficiency was in agreement with presented experimental result. However, CO conversion simulation result was not well predicted compared with presented experimental result. This is because FLUENT 6.0 surface reaction does not take surface coverage into account. Simulation of exhaust gas temperature showed that it is not advisable to place the catalytic converter below 25cm or above 80cm from the engine outlet. It is found that CFD FLUENT 6.0 can be used to simulate surface reaction on a single channel by adjusting the Arrhenius constants by a factor of 10-15 for CO reaction and factor of 10-16 for NO reaction.